(untitled) (Revista Argentina de Musicología, 2018)
In this paper we analyze the changes that occurred in the professional folklore in Argentina, and more precisely in the chacarera, after the inclusion of the drum kit as a rhythmic-percussive instrument. The hypothesis is that this shift is significant because it causes a change in the textural function of the percussion accompaniment, transforming a hierarchical feature in the constitution of these genres. In this sense, we can state that this modification has been a major aesthetic change in the folk scene. First, the paper addresses some notions that are relevant to our argument such as the idea of ‘hierarchy’ on the traits that define the genre; the notion of “textural function”; and rhythmic characteristics of the chacarera and other ternary genres in the argentine folklore. Subsequently we present some artists and albums that pioneered the incorporation of the drum kit in this repertoire prior to the 1990. Finally, given that the source of the use of the set of drums in professional folklore and other scenes, came from rock, we will expose some characteristics ot the textural patterns and other functions of the drums in rock music, in order to have the necessary elements to introduce the central argument of the work: the rhythmic-textural change in the folk scene.